2023
DOI: 10.3390/ijms24087553
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA Biomarker for Detecting Breast Cancer in High-Risk Benign Breast Tumors

Abstract: High-risk benign breast tumors are known to develop breast cancer at high rates. However, it is still controversial whether they should be removed during diagnosis or followed up until cancer development becomes evident. Therefore, this study sought to identify circulating microRNAs (miRNAs) that could serve as detection markers of cancers arising from high-risk benign tumors. Small RNA-seq was performed using plasma samples collected from patients with early-stage breast cancer (CA) and high-risk (HB), modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…In breast cancer tissues, decreased amounts of miRNA-128 were associated with poor clinical therapeutic efficacy and patients' survival rates [59,63]; whereas the TCGA clinical database revealed that miRNA-128 was overexpressed in patients and was associated with a better prognosis of breast cancer [64]. Low serum miRNA-128 levels were also identified as a potential biomarker able to detect breast cancer from high-risk benign tumors in only one study [41], further indicating a lack of research on the relationship between this circulating miRNA and breast cancer. Here, we propose, for the first time, a diagnostic value for decreased EV miRNA-128 levels in a pilot sample of patients with breast cancer, with 100% specificity, and sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In breast cancer tissues, decreased amounts of miRNA-128 were associated with poor clinical therapeutic efficacy and patients' survival rates [59,63]; whereas the TCGA clinical database revealed that miRNA-128 was overexpressed in patients and was associated with a better prognosis of breast cancer [64]. Low serum miRNA-128 levels were also identified as a potential biomarker able to detect breast cancer from high-risk benign tumors in only one study [41], further indicating a lack of research on the relationship between this circulating miRNA and breast cancer. Here, we propose, for the first time, a diagnostic value for decreased EV miRNA-128 levels in a pilot sample of patients with breast cancer, with 100% specificity, and sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miRNA-27a relative expression levels seem to negatively correlate with hormonal receptor status [35]. 5, where the results each study are summarized in terms of biofluid type and comparison of the miRNA lev in the selected population [32][33][34][35][36][37][38][39][40][41][42]. According to our systematic review, miRNA-128 expression in biofluids appears to be underinvestigated.…”
Section: Systematic Review Of the Diagnostic Value Of Mirna-27a And M...mentioning
confidence: 92%
See 2 more Smart Citations
“…The search for predictive biomarkers useful to draw further distinctions among BC subtypes is an active field of research that includes genomic, proteomic and/or machine learning approaches. In recent years, epigenetic biomarkers have gained growing attention, especially micro-RNAs (miRNA or miR) that have been predicted (and in some cases, validated) as very promising BC markers [ 49 , 50 , 51 ] for early detection as well [ 52 , 53 , 54 ]; notably, some studies also concentrated on circulating miR, opening the way towards a minimally invasive diagnostic approach [ 55 , 56 , 57 , 58 ].…”
Section: Clinical Features Of Bcmentioning
confidence: 99%